2011
DOI: 10.1002/ajmg.a.34057
|View full text |Cite
|
Sign up to set email alerts
|

Further expansion of the phenotypic spectrum associated with mutations in ALDH18A1, encoding Δ1‐pyrroline‐5‐carboxylate synthase (P5CS)

Abstract: We report on the third case of cutis laxa and progeroid features caused by a homozygous mutation in ALDH18A1 that encodes Δ¹-pyrroline-5-carboxylate-synthase (P5CS). This severely affected child, born to consanguineous parents of Pakistani origin, presented with lax, wrinkled and thin skin with dilated and tortuous subcutaneous blood vessels, corneal clouding, and hypotonia. The child had severe global developmental delay and feeding difficulties and died in infancy for an unknown reason. The proband was homoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 13 publications
4
70
0
Order By: Relevance
“…So far, only 13 affected individuals with ALDH18A1 mutations from seven unrelated families have been described, mainly with missense or splice site mutations [11,14,16,17,[22][23][24]. The~1.6 kb microdeletion identified here is the first mutation of this class found in ALDH18A1-related CL.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…So far, only 13 affected individuals with ALDH18A1 mutations from seven unrelated families have been described, mainly with missense or splice site mutations [11,14,16,17,[22][23][24]. The~1.6 kb microdeletion identified here is the first mutation of this class found in ALDH18A1-related CL.…”
Section: Discussionmentioning
confidence: 82%
“…However, the intracranial arterial malformation of patient 2 is previously unreported and had dramatic consequences. In two patients with ALDH18A1-related CL, kinky tortuosity of brain vessels was reported [16,17] demonstrating that in this severe form of CL vessels are especially vulnerable. Therefore, vessels should not only be assessed in ADCL, ARCL1, and ATS that are well known for their arterial malformations [1,18,19], but also in proline biosynthesis pathologies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…21,22,38,42,43 The two patients, presented by Baumgartner et al, 22 showed low ornithine, arginine, citrulline and proline. Except for low ornithine levels in two of the patients described by Bicknell et al, 21 no amino-acid profile abnormalities have been described in the other patients.…”
Section: Metabolic Abnormalitiesmentioning
confidence: 94%
“…In this first family, P5CS deficiency was a slowly progressive neurodegenerative disorder affecting both the central and peripheral nervous system, combined with cataracts and extensive connective tissue involvement. However, the majority of patients with P5CS deficiency subsequently reported were shown to have a cutis laxa syndrome (Bicknell et al 2008, Skidmore et al 2011, Martinelli et al 2012.…”
Section: Infantile Cutis Laxa Phenotypementioning
confidence: 99%